Pengaruh Pengungkapan Environmental, Social, and Governance (ESG) terhadap Manajemen Laba pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2020–2024 - Vutri Anggraeni; Susi Sarumpaet (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) disclosure on earnings management in mining companies listed on the Indonesia Stock Exchange during the 2020–2024 period. ESG disclosure has received increasing attention from stakeholders because it is considered to enhance corporate transparency, accountability, and sustainability, thereby potentially influencing earnings management practices. This research employed a quantitative approach using secondary data obtained from companies' annual reports and sustainability reports. The sample was selected using purposive sampling, resulting in 33 companies with a total of 165 panel observations. Data were analyzed using panel data regression with the Common Effect Model (CEM). Earnings management was measured using the Modified Jones Model, while ESG disclosure was assessed using the ESG Disclosure Index. The findings indicate that ESG disclosure does not have a significant effect on earnings management in mining companies. In addition, the control variables firm size, leverage, and profitability (ROA) demonstrate different effects on earnings management. These results suggest that ESG disclosure has not yet become an effective governance mechanism for limiting earnings management practices. This finding implies that ESG reporting remains primarily oriented toward regulatory compliance and stakeholder expectations rather than improving financial reporting quality and reducing managerial opportunistic behavior.Top of Form.Bottom of Form